Individual difference in acts of self-sacrifice. (27th December 2018) - Stagnaro, Michael N.; Littman, Rebecca; Rand, David G.
Abstract: Whitehouse's model explains when people engage in self-sacrifice, but not who is most likely to do so. We propose incorporating individual differences, such as cognitive style (one's inclination toward intuition versus deliberation), and argue that individuals who rely on intuition may be more likely to (1) develop group identity fusion after an emotional experience and (2) engage in pro-social self-sacrifice.